The ribosome assembly GTPase EngA is involved in redox signaling in cyanobacteria - Llop, Antonio; Bibak, Sirine; Cantos, Raquel; Salinas, Paloma; Contreras, Asunción (Frontiers in Microbiology, 2023)
Photosynthetic organisms must cope with environmental challenges, like those imposed by the succession of days and nights or by sudden changes in light intensities, that trigger global changes in gene expression and metabolism. The photosynthesis machinery is particularly susceptible to environmental changes and adaptation to them often involves redox-sensing proteins that are the targets of reactive oxygen species generated by photosynthesis activity. Here we show that EngA, an essential GTPase and ribosome-assembly protein involved in ribosome biogenesis in bacteria and chloroplasts, also plays a role in acclimatization to environmentally relevant stress in Synechococcus elongatus PCC7942 and that PipX, a promiscuous regulatory protein that binds to EngA, appears to fine-tune EngA activity. During growth in cold or high light conditions, the EngA levels rise, with a concomitant increase of the EngA/PipX ratio. However, a sudden increase in light intensity turns EngA into a growth inhibitor, a response involving residue Cys122 of EngA, which is part of the GD1-G4 motif NKCES of EngA proteins, with the cysteine conserved just in the cyanobacteria-chloroplast lineage. This work expands the repertoire of ribosome-related factors transmitting redox signals in photosynthetic organisms and provides additional insights into the complexity of the regulatory interactions mediated by EngA and PipX.